TANGGUNG JAWAB AWAM DALAM PERUTUSAN DIAKONIA GEREJA - Norbertus Jegalus (Program Studi Filsafat Agama Universitas Katolik Widya Mandira Kupang, 2020)
Laymen in the Church have an unique mission in the world. They are sent by Christ the Lord to transform the world with the christian values. They have a great responsability in spreaching the Gospel to all people. In cooperation with the clergy, they should realize Jesus' teaching of love in the act of loving to each other, especially the sick, the poor, the suffer. They should promote human rights, justice, peace and common wealth in the society where they live. This is their mission based on the faith, Gospel and The Social Teaching of the Church. This mission is a form of diaconia of the laymen in the Church.